PENGAWASAN PERIZINAN USAHA PERKEBUNAN KELAPA SAWIT DI KABUPATEN KUANTAN SINGINGI - Eca Pamela; Zaili Rusli SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Kuantan Singingi District Government supervises permits that apply to permit holders in carrying out activities carried out for licenses owned. The supervision of the oil palm plantation businnes by thr Agriculture Office of Kuantan Singingi Regency was carried out in the benthic administration of plantation business licenses. The phenomenon that arises in this supervision is still weak supervision by the Agriculture Sevice and there are still many problems encountered in the licensing of oil palm plantation businesses. The purpose of this study is to find out how the supervision by the Agriculture Service on oil palm plantation business permits and what are the inhibiting factors in the supervision of business permits for oil palm plantations. The theoritical concept used in this research is Stoner’s concept of supervision which consist of determining standards and methods of perfomance assessment, perfomance appraisal, comparing performance with standars and taking corrective actions. The selection of this informant uses purposive sampling. The result of this study indicate that supervision of the Department of Agriculture has not been optimal, the lack of time standars in conducting direct supervision to the field which is not yet effective, and also the inhibiting factors in conducting supervision are human resource and funds or cost.